Real time PCR. Application in dengue studies (Colombia Medica, 2011)
PCR (polymerase chain reaction) is a routinely used tool in every diagnostic and research laboratory. This technique has been used in detection of mutations and pathogens, forensic investigation, and even is the base tool for human genome sequencing. A modification of PCR technique, real time PCR, allows the quantification of nucleic acids with higher sensibility, specificity and reproducibility. This article is intended to clarify the foundations of real-time PCR, using an application model for virology. In the actual work, it was quantified the viral load of dengue virus serotype 2 produced from infected murine macrophages; the obtained results in this work established that murine strain BALB/c presents a greater susceptibility to dengue virus infection, which establishes BALB/c murine strain as a best model of study for investigation of dengue virus infection physiopathology.